Synthetic Red Blood Cell-Specific Glycolytic Intermediate 2,3-Diphosphoglycerate (2,3-DPG) Inhibits Plasmodium falciparum Development In Vitro - Morais, Inês; Medeiros, Márcia M.; Carvalho, Maria; Morello, Judit; Teixeira, Sara M.; Maciel, Suelma; Nhantumbo, Janice; Balau, Ana; Rosa, Margarida T. G.; Nogueira, Fátima; Rodrigues, João Alexandre; Carvalho, Filomena A.; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Mechanisms of malaria parasite interaction with its host red blood cell may provide potential targets for new antimalarial approaches. Pyruvate kinase deficiency has been associated with resistance to malaria in both experimental models and population studies. Two of the major pyruvate kinase deficient-cell disorders are the decrease in ATP and the increase in 2,3-biphosphoglycerate (2,3-BPG) concentration. High levels of this metabolite, only present in mammalian red blood cell, has an inhibitory effect on glycolysis and we hypothesized that its accumulation may also be harmful to the parasite and be involved in the mechanism of protection provided by that enzymopathy. We examined the effect of a synthetic form, 2,3-DPG, on the Plasmodium falciparum intraerythrocytic developmental cycle in vitro. Results showed an impairment of parasite growth with a direct effect on parasite maturation as significant lower progeny emerged from parasites that were submitted to 2,3-DPG. Further, adding the compound to the culture medium did not result in any effect on the host cell, but instead the metabolic profile of an infected cell became closer to that of a non-infected cell.